2020
DOI: 10.1088/1361-6560/ab831a
|View full text |Cite
|
Sign up to set email alerts
|

Low-dose CT with deep learning regularization via proximal forward–backward splitting

Abstract: Low dose X-ray computed tomography (LDCT) is desirable for reduced patient dose. This work develops image reconstruction methods with deep learning (DL) regularization for LDCT. Our methods are based on unrolling of proximal forward-backward splitting (PFBS) framework with data-driven image regularization via deep neural networks. In contrast with PFBS-IR that utilizes standard data fidelity updates via iterative reconstruction (IR) method, PFBS-AIR involves preconditioned data fidelity updates that fuse analy… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 39 publications
0
25
0
Order By: Relevance
“…By using GAN framework and incorporating information on target standard dose images from a data distribution, the proposed method has a potential to reduce noise in LDCT images for unpaired CT images or even for a complicated noise model. 30 Ding et al 31 proposed a method that unrolls the optimisation by PFBS (proximal forward-backward splitting) with datadriven image regularisation learned by DNN. To further improve image reconstruction quality, a preconditioned PFBS version was used with fused analytical and iterative reconstruction (AIR) and as a result, it was suggested that deep learning regularised methods PFBS-IR (proximal forward-backward splitting via iterative reconstruction) and PFBS-AIR (proximal forward-backward splitting via analytical and iterative reconstruction) provided better reconstruction quality compared to conventional wisdoms (AR or IR), and DL-based post processing method (FBPConvNet 31 ) (Table 2).…”
Section: Image Noise Reductionmentioning
confidence: 99%
See 2 more Smart Citations
“…By using GAN framework and incorporating information on target standard dose images from a data distribution, the proposed method has a potential to reduce noise in LDCT images for unpaired CT images or even for a complicated noise model. 30 Ding et al 31 proposed a method that unrolls the optimisation by PFBS (proximal forward-backward splitting) with datadriven image regularisation learned by DNN. To further improve image reconstruction quality, a preconditioned PFBS version was used with fused analytical and iterative reconstruction (AIR) and as a result, it was suggested that deep learning regularised methods PFBS-IR (proximal forward-backward splitting via iterative reconstruction) and PFBS-AIR (proximal forward-backward splitting via analytical and iterative reconstruction) provided better reconstruction quality compared to conventional wisdoms (AR or IR), and DL-based post processing method (FBPConvNet 31 ) (Table 2).…”
Section: Image Noise Reductionmentioning
confidence: 99%
“…It then learns the proper gradient of the low-dose CT in a pure unsupervised manner. 29 Another solution was developed by Ding et al 31 with a similar idea to the iterative reconstruction method, but changed to a deep learning based regularisation method for low-dose CT image reconstruction. It was shown to have a better reconstruction quality than analytical reconstruction or iterative reconstruction techniques.…”
Section: Capability Of Deep Learning Networkmentioning
confidence: 99%
See 1 more Smart Citation
“…The fundamental reason is mainly through the calculation of any non-convex prior with a large amount of calculation, which leads to complex optimization algorithms. What's more, the parametric assumptions on blur kernels could greatly improve the robustness of blind image deblurring [19,20], a principled algorithm within the maximum a posterior framework to tackle image restoration with a partially known or inaccurate degradation model [21], and other deep learning and other methods that contain a large number of real image sets and training sets using self-supervised methods [22][23][24][25][26], the characteristics of training data sets are often It will greatly affect the performance of the entire model, and in many cases, the construction and processing of data sets are often very expensive and low feasibility.…”
Section: Image Deblurringmentioning
confidence: 99%
“…It has been shown that various types of deep neural networks are capable of suppressing the noise in low-dose computed tomography (CT) as well as positron emission tomography (PET) images leading to dependable estimation of the standard-dose images [9,[22][23][24][25][26][27][28][29]. Likewise, a number of studies have been conducted in the field of lowdose SPECT-MPI.…”
Section: Introductionmentioning
confidence: 99%